PEMBACAAN EPISTEMOLOGI ILMU TAFSIR KLASIK - Muhamad Ali Mustofa Kamal (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2016)
This study focuses on the question of the reconstruction of the epistemological interpretation of classical exegesis by offering model mapping study of classical interpretation. The method used is based literary exploratory-qualitative approach. Epistemology of classical interpretation rely solely on aspects of history since the time of the Prophet, his tabi'in and generations before the contemporary era that emphasizes the validity of the interpretation of history rather than on naql aspects than aql aspects (ra'yu). The Reconstruction for methodological interpretation at all times would be covered by the circumstances that surround the commentators. The method will continue to grow with different perspectives of the commentators in the condition and situation with other commentators. Interpretation will continue to move as long as science itself is constantly moving and human culture is not going nowhere.